Mesoscopic physics of complex materials - Chow T S (New York Springer-Verlag, 2000)
A cross-disciplinary study of the physical properties of complex fluids, solids, and interfaces as a function of their mesoscopic structures, with empasis on nonequilibrium phenomena. The book introduces readers to the methods of non-equilibrium statisti
Keywords: Mesoscopic phenomena(Physics)